Assessments of fodder values of 3 indigenous and 1 exotic woody plant species in the highlands of central Ethiopia - Mekonnen, Kindu; Glatzel, G.; Sieghardt, M. (International Mountain Society (IMS) and United Nations University, 2009)
Leaves and twigs of indigenous woody plant species are used as a source of supplemental animal feed in the mountainous landscapes of central Ethiopia. A study was carried out from 2004 to 2006 to assess the nutritional value of three indigenous and one exotic species, based on the chemical composition, tannin contents, in vitro dry matter digestibility, and digestible energy. The species studied were Hagenia abyssinica (Bruce) J.F. Gmel., Dombeya torrida (J.F. Gmel.) P. Bamps, Buddleja polystachya Fres., and Chamaecytisus palmensis (Christ) Bisby & K. Nicholls. The first three are indigenous, and the last one is an exotic species. The Na content of the foliage and flower bud in the four species was much lower than the minimum requirement for ruminants, while other micro- and macronutrients were within the recommended range of nutrient concentrations in animal feeds. On the other hand, the crude protein content of the foliage and flower bud in the four fodder species was higher than the minimum required level. The foliage and flower bud in vitro dry matter digestibility of H. abyssinica and C. palmensis was 70% and 71%, respectively. The digestible energy of the foliage of H. abyssinica and C. palmensis was significantly higher than the digestible energy of D. torrida and B. polystachya. Therefore, the foliage and flower bud of most of those species can be used as sources of supplemental fodder with a proper feeding management scheme.